Privatisation A Challenge for Sub-Saharan Africa - Wegner, Lucia (OECD Development Centre Policy Insights, 2005)
Thirty-eight sub-Saharan African countries have implemented privatisations programmes. The privatisation process is still far from complete and has led to mixed results. The lessons learned from past privatisations allow the identification of elements that could contribute to future success